2006
DOI: 10.1016/j.ejcts.2005.10.029
|View full text |Cite
|
Sign up to set email alerts
|

The non-circular shape of FloWatch®-PAB prevents the need for pulmonary artery reconstruction after banding.Computational fluid dynamics and clinical correlations

Abstract: The non-circular shape of FloWatch-PAB can replace conventional circular banding with the following advantages: (a) the pressure gradient will remain essentially the same as for conventional circular banding for any given cross-section, but with significantly smaller reduction of PA perimeter; and (b) PA reconstruction at the time of de-banding for intra-cardiac repair can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 23 publications
3
67
1
Order By: Relevance
“…Based upon their observations, Corno and associates suggested that (1) FW-PAB eliminates the need for reoperation to adjust the PAB, not only in the early postoperative period but for as long as 3 years after hospital discharge; (2) postoperative management is simplified and the durations of postoperative mechanical ventilation, ICU stay, and hospital stay are significantly reduced, particularly in more compromised and difficult to manage infants, such as the ones with associated anomalies; (3) the cost of the device is more than offset by the reduction in duration of postoperative mechanical ventilation, length of stay in the ICU and in the hospital, and avoidance of any PAB-related reoperation; and (4) pulmonary artery reconstruction is not required when intracardiac repair is undertaken. 30 Our experience, as reported here, has not affirmed all of the potential advantages of FW-PAB touted by others on the basis of their own observations. We acknowledge the theoretical advantage of FW-PAB for ''ventricular retraining'' purposes, although we have used it only once in such a setting and the surgical literature to date does not describe use of such a device in more than a few instances.…”
Section: Discussioncontrasting
confidence: 78%
“…Based upon their observations, Corno and associates suggested that (1) FW-PAB eliminates the need for reoperation to adjust the PAB, not only in the early postoperative period but for as long as 3 years after hospital discharge; (2) postoperative management is simplified and the durations of postoperative mechanical ventilation, ICU stay, and hospital stay are significantly reduced, particularly in more compromised and difficult to manage infants, such as the ones with associated anomalies; (3) the cost of the device is more than offset by the reduction in duration of postoperative mechanical ventilation, length of stay in the ICU and in the hospital, and avoidance of any PAB-related reoperation; and (4) pulmonary artery reconstruction is not required when intracardiac repair is undertaken. 30 Our experience, as reported here, has not affirmed all of the potential advantages of FW-PAB touted by others on the basis of their own observations. We acknowledge the theoretical advantage of FW-PAB for ''ventricular retraining'' purposes, although we have used it only once in such a setting and the surgical literature to date does not describe use of such a device in more than a few instances.…”
Section: Discussioncontrasting
confidence: 78%
“…2), and normalized wall pressure difference along the length of the domain. The axial component of the velocity u z is normalized with respect to the average axial velocity at the inlet ū i : (30) where Q is the volumetric flow rate calculated from the throat Reynolds number (see table I). The pressure difference data are normalized with respect to the average velocity at the throat ū t : (31) where p z denotes the wall pressure along the z axis and p z=0 is the wall pressure at z = 0.…”
Section: The Fda Benchmarkmentioning
confidence: 99%
“…Despite the fact that CFD was originally developed for industrial and engineering purposes, in recent years applications in the biomedical field have also attracted considerable attention (Xu et al 2006), aided by the increasing power of computers (Politis et al 2007). CFD has been previously applied to investigate several problems in the cardiovascular and the respiratory system (Pekkan et al 2005, Yoganathan et al 2005, Corno et al 2006, Jung et al 2006, van Tricht et al 2006, Xu et al 2006, Yang et al 2006a,b, Politis et al 2007.…”
Section: Introductionmentioning
confidence: 99%